Glioblastoma-Derived Exosomes as Nanopharmaceutics for Improved Glioma Treatment - Hyeji Lee; Kanghye Bae; Ah-Rum Baek; Eun-Bin Kwon; Yeoun-Hee Kim; Sung-Wook Nam; Gang Ho Lee; Yongmin Chang (MDPI AG, 2022)
The use of cancer-derived exosomes has been studied in several cancer types, but the cancer-targeting efficacy of glioma-derived exosomes has not been investigated in depth for malignant glioblastoma (GBM) cells. In this study, exosomes were derived from U87MG human glioblastoma cells, and selumetinib, a new anticancer drug, was loaded into the exosomes. We observed the tropism of GBM-derived exosomes in vitro and in vivo. We found that the tropism of GBM-derived exosomes is in contrast to the behavior of non-exosome-enveloped drugs and non-GBM-specific exosomes in vitro and in vivo in an animal GBM model. We found that the tropism exhibited by GBM-derived exosomes can be utilized to shuttle selumetinib, with no specific targeting moiety, to GBM tumor sites. Therefore, our findings indicated that GBM-derived exosomes loaded with selumetinib had a specific antitumor effect on U87MG cells and were non-toxic to normal brain cells. These exosomes offer improved therapeutic prospects for glioblastoma therapy.